Conformational Dynamics of the Hepatitis B Virus Pre-genomic RNA on Multiple Time Scales: Implications for Viral Replication. Issue 18 (30th September 2022) - Olenginski, Lukasz T.; Kasprzak, Wojciech K.; Bergonzo, Christina; Shapiro, Bruce A.; Dayie, Theodore K.
Graphical abstract: Highlights: HBV polymerase binds ε RNA to initiate HBV genome replication. Previous NMR studies hint that ε dynamics may be functional. NMR demonstrates motion on multiple time scales in mainly conserved nucleotides critical for function. MD simulations suggest that ε undergoes structural rearrangements that may be controlled by its priming loop. RNA dynamics are likely an integral part of HBV replication. Abstract: Human hepatitis B virus (HBV) replication is initiated by the binding of the viral polymerase (P) to epsilon (ε), an ≈85-nucleotide (nt) cis -acting regulatory stem-loop RNA located at the 5′-end of the pre-genomic RNA (pgRNA). This interaction triggers P and pgRNA packaging and protein-primed reverse transcription and is therefore an attractive therapeutic target. Our recent nuclear magnetic resonance (NMR) structure of ε provides a useful starting point toward a detailed understanding of HBV replication, and hints at the functional importance of ε dynamics. Here, we present a detailed description of ε motions on the ps to ns and μs to ms time scales by NMR spin relaxation and relaxation dispersion, respectively. We also carried out molecular dynamics simulations to provide additional insight into ε conformational dynamics. These data outline a series of complex motions on multiple time scales within ε. Moreover, these motions occur in mostly conserved nucleotides from structural regions (i.e., priming loop, pseudo-triloop, and U43 bulge) that biochemical and mutational studies have shown to be essential for P binding, P-pgRNA packaging, protein-priming, and DNA synthesis. Taken together, our work implicates RNA dynamics as an integral feature that governs HBV replication.